Comparative study of outcome following primary posterior sagittal ano-rectoplasty and primary anterior sagittal ano-rectoplasty for vestibular fistula - Saoji, Rajendra; Nagdeve, Nilesh G. (International Surgery Journal, 2018)
Background: To compare the postoperative complications and bowel function following primary PSARP and primary ASARP. Methods: This prospective study was carried out over a period of 4 years. Patients above 4 months, who needed surgical repair for vestibular fistula were included in study. They were randomly allocated into PSARP group and ASARP group. After surgical intervention, patients of both groups were compared with respect to post-operative complications, voluntary bowel control, constipation, need for laxatives. Results: 44 patients were enrolled in the study. Of these, 22 patients were allocated to primary PSARP group while remaining patients underwent ASARP. One patient from each group was lost to follow‑up and hence, excluded from the final analysis. The two groups were comparable with respect to age, maturity at birth, weight at the time of surgery, blood investigations. Total 16 patients had associated congenital anomalies. During the postoperative period, four patients from PSARP group and two patients from ASARP group had superficial wound infection of perineal incision which was managed conservatively. One patient in PSARP group had a major breakdown of perineal wound with retraction of pulled rectum which required colostomy. There was no recurrence of fistula in any patient. No patient had stenosis of neo-anus or anterior displacement of rectum. Functional assessment of bowel function was done in 25 patients who completed 3 years of age. Voluntary bowel movements were observed in 75% of cases in the ASARP group compared to 38 % in PSARP group. 15% patients of PSARP group and 7.5% patients with ASARP had soiling. Though the difference was not statistically significant, nearly 38% of the patients after PSARP, needed laxative for normal bowel habit compared to 8% patients in ASARP group. Conclusions: ASARP promises many advantages in the treatment of vestibular fistula in comparison to PSARP. Comparable post-operative complications, good cosmetic results, excellent continence with less need for laxatives are the advantages of ASARP.